Inter-Segmental Foot Kinematics During Gait in Elderly Females with Symptomatic and Asymptomatic Hallux Valgus - Doojae Lee MD (Foot & Ankle Orthopaedics, 2016)
Category: Basic Sciences/Biologics Introduction/Purpose: Hallux valgus (HV) is a common condition that may lead to considerable pain and disability. While a number of gait analyses of people with and without HV have been performed using planter pressures, the results to date are not in agreement. In the last two decades, several multi-segmental foot models (MFMs) have been introduced for the in vivo analysis of dynamic foot kinematics. Although there are some investigations about triplanar multisegmental of patients with HV, there were lack of age and gender matched comparison of inter-segmental foot motions in previous reports. The objective of this study was to find the effect of hallux valgus deformity on inter-segmental motion of the foot by comparisons with age and gender controlled healthy adults using a multi-segmental foot model (MFM) with 15-marker set. Methods: Eighteen female symptomatic hallux valgus patients (SHV group) and 50 female symptom-free older female participants who had normal function of the foot and ankle and no radiographic evidence of osteoarthritis were included in this study. Symptom-free participants were divided into asymptomatic hallux valgus group (AHV, n=14) and control group (CON, n=36). For radiographic examinations, hallux valgus angle was measured using standing anteroposterior radiograph of the foot. The temporal gait parameters such as the cadence, speed, stride length, step width, step time, and proportion of stance phase were calculated. Segmental foot kinematics evaluated using a 3D MFM of a 15-marker set (Foot3D model). Inter-segmental angles (ISA) (hindfoot relative to tibia, forefoot to hindfoot, and hallux to forefoot) were calculated at each time points (100 time points for whole gait cycle). The ISAs (position) at specific phases of gait cycle, the change of ISA (motion) between phases and range of ISAs during the whole gait cycle were calculated and compared among groups. Results: Basic demographic data was no significant difference among groups except HV angle and foot width. The speed, stride length were significantly lower in SHV group. The proportion of the stance phase in a gait cycle was longer SHV group. Range of motion (ROM) of sagittal plane of hallux and transverse plane of forefoot was lower in SHV group. Significantly different finding in SHV group included more dorsiflexed position of hallux segment, reduced forefoot abduction motion during terminal stance and loss of push off during preswing(Figure 1). However, when we compared AHV group and CON group, there was no difference in temporal gait parameters and ROM of inter-segmental motions of foot. Hallux segment was in more valgus position and the forefoot segment was in more pronated position in AHV group than in CON group. Conclusion: Symptomatic hallux valgus patients showed different gait parameters & inter-segmental motion during gait when compared with age-matched controls. Asymptomatic hallux valgus does not affect gait & inter-segmental motion during gait except that the hallux segment was in more valgus position and the forefoot segment was in more pronated position. The results of this study suggest that effect of moderate hallux valgus itself on foot kinematics might be limited while pain or arthritic change of the joint might cause changes in gait in patients with symptomatic HV.